PENGARUH PERILAKU BERKARAKTER SISWA KELAS VIII TERHADAP HASIL BELAJAR PPKN DI SMP NEGERI 1 TEMPULING KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Juraidah '; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research is motivated by the process of teaching and learning activities that are part of the educational process, but in the process of teaching and learning takes many students bored and out of the classroom during class hours, To form a good character is not enough just to go through the process of learning in the classroom Citizenship, but it must also be accompanied by good habits performed in daily life. Teach character values not only at the cognitive level, but touches on internalization, and the real practice in the lives of young people in the community every day. At each school the student learning outcomes in get KKM sometimes substandard schools or some children are not in either study results obtained from the daily tests and exams semester. The wording in this study is "What does behavior of the character on the learning outcomes of students in SMP Negeri 1 PPKn Tempuling, District Tempuling, Indragiri Downstream"?. This study aims to determine whether there are behavioral effects on learning outcomes of students in SMP Negeri 1 character PPKn Tempuling District Tempuling, Indragiri Hilir. The population and the sample in this study is the eighth grade students of SMP N 1 Tempuling amount of 95 students. While sampling technique using saturated samples, namely 95orang eighth grade students of SMP Negeri 1 Tempuling. The data were collected through observation, questionnaires, interviews and technical literature. When analyzing the data using quantitative descriptive. Thereafter, the data were analyzed with the aid of statistical tests using SPSS version 17. The results obtained can be calculated F (1001) ≤ F table (3.94) with Sig. concluded (0320) ≥ (0.05). Thus, Ho is rejected and Ha accepted. That is, the influence of behavior on learning outcomes of students marked PPKn is not significant.Key word: Character Behaviour, Learning Outcomes